2020
DOI: 10.1037/pst0000198
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous system synchrony: An exploratory study of its relationship with the therapeutic alliance and outcome in couple therapy.

Abstract: We thank Jarno Mikkonen for his help in coding MATLAB scripts, and Petri Kinnunen and Lauri Viljanto for assisting in technical issues related to the study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 66 publications
1
32
1
Order By: Relevance
“…Comparing the three different types of dyads (client-client, client-therapist, therapist-therapist) revealed that the co-therapists had indeed more head and body synchrony than the other kinds of dyads. Previous research on the same data also found a large amount of physiological synchrony (electrodermal activity) between co-therapists (Karvonen et al, 2016;Tourunen et al, 2020). The large amount of synchrony between the co-therapists can be interpreted as them being bodily involved similarly in the situation, in listening to the clients' problems, and in trying to help them through their professional roles.…”
Section: Discussionmentioning
confidence: 65%
“…Comparing the three different types of dyads (client-client, client-therapist, therapist-therapist) revealed that the co-therapists had indeed more head and body synchrony than the other kinds of dyads. Previous research on the same data also found a large amount of physiological synchrony (electrodermal activity) between co-therapists (Karvonen et al, 2016;Tourunen et al, 2020). The large amount of synchrony between the co-therapists can be interpreted as them being bodily involved similarly in the situation, in listening to the clients' problems, and in trying to help them through their professional roles.…”
Section: Discussionmentioning
confidence: 65%
“…Early family therapy practice was distinguished by a willingness to embrace new technologies (tape recorder, film camera, one‐way screen), and some in the profession continue to innovate (e.g. Lee et al ., 2010; McHugh et al ., 2010; Tourunen et al ., 2020; . However, prior to COVID‐19 this mantle had largely been handed on to others; the use of virtual realities (VR) to help with social anxiety and ‘avatar therapy’ for psychosis are perhaps the best‐known recent examples of this (see Aali et al ., 2020 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Up to recently, PS in peripheral physiological measures has been studied mainly as a metric of some form of affective connectedness between individuals (reviewed by Palumbo et al, 2017). Examples include peripheral PS in therapist-patient dyads as a measure of psychotherapy success (Koole et al, 2020), in couples in marital counseling as a measure of therapy outcome (Tourunen et al, 2019) and as measure of collaborative learning (Malmberg et al, 2019). Positive results found in these contexts may (partly) be driven by shared attentional engagement to external events, as connectedness between people may be strongly associated with mutual attentiveness (Tickle-Degnen and Rosenthal, 1990).…”
Section: Introductionmentioning
confidence: 99%